EXPLORING STUDYTWT AS AN ONLINE PLATFORM FOR LEARNING ENGLISH ON TWITTER - Fitri Ramdani; Aris Dwi Intan Aprianti (GLOBAL: Education Language and Humanity Journal, 2024)
This study explores how users of StudyTwt engage with the platform as a tool for learning English and examines how it supports their language acquisition. Using a qualitative research approach, the study applied interviews and observation with eight participants who have actively used Twitter to study English and maintain StudyTwt accounts. The research identifies three main ways that StudyTwt serves as a resource for English learners: first, by allowing users to find and share various English learning materials; second, by providing opportunities to connect with study partners and participate in discussion groups; and third, by offering a source of motivation and entertainment. In terms of how StudyTwt facilitates English learning, the study highlights two primary benefits: fostering interactive and collaborative learning experiences, and providing users with easy access to flexible, personalized learning opportunities. The findings suggest that StudyTwt can be a useful educational tool, demonstrating the potential of social media platforms to enhance language learning through structured collaboration, accessible resources, and user-driven content.